DNA metabarcoding of feces for diet analysis of little auks and other Arctic seabird species in Svalbard ... - de Leeuw, Joep; van den Brink, Xantia; Gabrielsen, Geir; Nijland, Reindert (MDA, 2024)
Feces samples taken at Svalbard were sequenced using COI and 18S metabarcoding for diet analysis. Species included in this study: black-legged kittiwake (Rissa tridactyla), Brünnich’s guillemot (Uria lomvia) and little auk (Alle alle). ... : DNA metabarcoding reveals high diversity of fish and macrofaunal species in diets of little auks and other Arctic seabird species in Svalbard. The aim of this study was to test the use of DNA metabarcoding in faeces of Arctic seabird species to assess diet composition, and its potential application as indicator for marine ecosystem status and food conditions for seabirds of the High Arctic. Diet diversity was determined using COI and 18S DNA metabarcoding, using Oxford Nanopore Sequencing, from faeces collected at breeding colonies of three focal species representing different parts of the food web: black-legged kittiwake (Rissa tridactyla), Brünnich’s guillemot (Uria lomvia) and little auk (Alle alle). This research was executed by Wageningen Marine Research and Wageningen University. ...